Answering questions with data Introductory Statistics for Psychology Students - Crump, Matthew J. C. (Open textbook library., 2018)
This is a free textbook teaching introductory statistics for undergraduates in Psychology. This textbook is part of a larger OER course package for teaching undergraduate statistics in Psychology, including this textbook, a lab manual, and a course website. All of the materials are free and copiable, with source code maintained in Github repositories.